2020
DOI: 10.3390/nu12123831
|View full text |Cite
|
Sign up to set email alerts
|

Digestible Indispensable Amino Acid Scores (DIAAS) of Six Cooked Chinese Pulses

Abstract: Values for the digestible indispensable amino acid score (DIAAS) of a protein are based on true ileal amino acid (AA) digestibility values obtained in adult humans or in the growing pig as an animal model. An experiment was conducted using growing pigs to determine the true ileal digestibility (TID) values of AA in six cooked Chinese pulses (kidney bean, mung bean, adzuki bean, broad beans, peas and chickpeas). Each pulse was included in a diet as the only source of crude protein (CP). An N-free diet was given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 28 publications
8
24
1
Order By: Relevance
“…The quantity and quality of protein are both determinants of the adequacy of diets, for meeting protein requirements [6] and the amino acid requirements of the human depend upon age and physiological state [36]. The DIAAS values of the cereals and pulses determined here were within the range of published values [15,22,[27][28][29][30][31]37,38]. Given that lysine was often the first-limiting amino acid, it was interesting to note the effect of the reactive lysine content on DIAAS.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The quantity and quality of protein are both determinants of the adequacy of diets, for meeting protein requirements [6] and the amino acid requirements of the human depend upon age and physiological state [36]. The DIAAS values of the cereals and pulses determined here were within the range of published values [15,22,[27][28][29][30][31]37,38]. Given that lysine was often the first-limiting amino acid, it was interesting to note the effect of the reactive lysine content on DIAAS.…”
Section: Discussionsupporting
confidence: 66%
“…The concentrations of AA in the cereals and pulses used here were within the range of published values [15,[27][28][29][30][31]. AAs in cereals are mainly stored in the starchy endosperm of cereals, in the form of prolamins and glutenins [32][33][34].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…For pork belly, skim milk powder, and soy flour, digestible levels of all IAAs were above the requirements, which translates into DIAAS values > 100%. However, DIAAS values are calculated based on the IAAlim and fails to highlight that other IAAs are present in further excess, and could thus act as : cut-off for actual requirement as a combination of amino acid content and digestibility of the respective indispensable amino acid; (A; data from [76]), skim milk powder (B; data from [57]), soy flour (C; data from [57]), rice (D; data from [80]), cooked peas (E; data from [87]) and maize (F; data from [80]).…”
Section: Food Groupmentioning
confidence: 99%
“…A recent article reported a study on the true digestibility values (percentage of the total indispensable AA from ileal extracts) of some Chinese pulses. The results of the experiment in humans older than 3 years to adults shows that DIAAS was 88% for kidney bean, 86% for mung bean, 76% for chickpeas, 68% for peas, 64% for adzuki bean and 60% for broad beans [32]. In another study, Kashyap et al [33] used the isotopic method to estimate DIAAS for mung bean and reported that the true mean ileal IAA digestibility of mung bean was 70.9 ± 2.1% after dehulling, demonstrating inconsistencies in methodologies of amino acid digestibility and indicating research gaps and need for elaborate datasets for seed dietary protein measurements to meet the quality challenge in the development of grain-based proteins [33].…”
Section: Seed Sources Of Dietary Proteinsmentioning
confidence: 99%